Spór o Muzeum Faszyzmu w Predappio. Public history in situ po włosku - Podemski, Piotr (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych Instytut Historyczny, 2022)
The Museum of Fascism in Predappio was never inaugurated, and yet an animated debate around its project constitutes a prime source material for public history scholars, not only in relation to Italy. The author discusses the status of Benito Mussolini’ shome town as a “sanctuary of fascism” in contemporary Italy, tolerated by the state. He subsequently outlines the project of the museum in question as well as the lines of argumentation by both sides of the national debate on the topic. While explaining the reasons why the Predappio project was finally abandoned, the author argues that this debate is a remarkable example of what John Foot has defined as “Italy’s divided memory”.
Keywords: public history